Web Application Development with R Using Shiny - Second Edition. - Beeley, Chris (Packt Publishing, Limited, 2016)
Integrate the power of R with the simplicity of Shiny to deliver cutting-edge analytics over the WebAbout This Book Use Shiny's built-in functions to produce engaging user interfaces, and integrate them into your own web pages Implement powerful user-contributed packages to access graphics from the web, make your own dashboards, use interactive maps, and more Extend Shiny using JavaScript and jQuery with minimal coding using this handy, step-by-step guideWho This Book Is ForThis book is for anybody who wants to produce interactive data summaries over the web, whether you want to share them with a few colleagues or the whole world. No previous experience with R, Shiny, HTML, or CSS is required to begin using this book, although you should possess some previous experience with programming in a different language. What You Will Learn Build interactive applications using Shiny's built-in widgets Use the built-in layout functions in Shiny to produce user-friendly applications Integrate Shiny applications with web pages and customize them using HTML and CSS Harness the power of JavaScript and jQuery to customize your applications Engage your users and build better analytics using interactive plots Debug your applications using Shiny's built-in functions Deliver simple and powerful analytics across your organization using Shiny dashboards Share your applications with colleagues or over the Internet using cloud services or your own serverIn DetailR is a highly flexible and powerful tool for analyzing and visualizing data. Most of the applications built using various libraries with R are desktop-based. But what if you want to go on the web? Here comes Shiny to your rescue!Shiny allows you to create interactive web applications using the excellent analytical and graphical capabilities of R. This book will guide you through basic data management and analysis with R through your first Shiny application, and then show you how to integrate Shiny applications with your own web pages. Finally, you will learn how to finely control the inputs and outputs of your application, along with using other packages to build state-of-the-art applications, including dashboards. Style and approachLearn by doing! Each chapter includes code and examples to use and adapt for your own applications. As the chapters progress, the code and examples are built upon until you have all the materials required to build a large, complex, real-world analytics application.